Pelatihan Keterampilan Bimbingan dan Konseling MBKM Guru TK MTA Jebres Surakarta - Hera Heru Sri Suryanti; Linda Dwi Sholikhah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
(1) Teachers at KB TK MTA Jebres in carrying out learning tasks are still constrained by several things including understanding MBKM, inclusive learning, guidance of students with problems, and planning of activity programs intended for normal children combined with ABK; (2) The purpose of community service activities with the theme of Guidance and Counseling Skills Training MBKM TK MTA Jebres, Surakarta is to provide knowledge and skills of Guidance and Counseling related to MBKM to Teachers to strengthen the role of guiding students in facing learning difficulties so that students achieve good achievements. (3) This community service is carried out by applying the Brenstorming method to explore teachers' opinions on problems related to MBKM, the Lecture method to deliver Guidance and Counseling material according to MBKM, the Question and Answer method to provide opportunities for teachers to exchange ideas, the Practice method to train teachers in implementing Guidance and Counseling according to MBKM and Case studies to provide space and time for teachers to convey the cases they have, so that the material is easily accepted by teachers and the training runs smoothly. The evaluation was carried out using a performance test (4) The results of the first training, all participants (Head of KB-TK MTA Jebres and Teachers) mastered MBKM, the main materials. The results of the second training, all participants (Head of KB-TK MTA Jebres and Teachers) mastered inclusive learning, guidance of students with problems, The results of the third training, all participants (Head of KB-TK MTA Jebres and Teachers) mastered the planning of activity programs intended for normal children combined with ABK.